Permainan Coding untuk Menstimulasi Kemampuan Berpikir Komputasional Anak Usia Dini : Tinjauan Pustaka - Widya Dwi Hardiyanti; Prayitno; Martha Christianti; Aprilia Rambe; Ulfiyani (Journal for Lesson and Learning Studies, 2025)
Many teachers in kindergarten do not know how to stimulate early childhood computational thinking ability. One way to stimulate early childhood computational thinking ability is through coding games, either using digital device media or without digital device media. This article aims to analyze the types of coding games as a medium that can help stimulate early childhood computational thinking ability. The method used is a systematic literature review using descriptive qualitative data analysis to analyze relevant previous studies. This study examined 40 articles on coding games to stimulate early childhood computational thinking ability in various international journals between 2020 and 2025. The results of the analysis of theoretical studies show that coding games can stimulate early childhood computational thinking ability. This is because coding games involve children getting used to thinking logically, being structured, processing tasks systematically, and solving problems by developing the right solutions. The implications of this study can provide an overview of the types of coding games that can be implemented or practiced by teachers to stimulate early childhood computational thinking ability, by adjusting facilities in schools can use digital media or without digital media.